The relationship between backpack load, shoulder muscle strength, and shoulder pain in elementary school students - Harzat; Gadis Meinar Sari; Mohammad Fathul Qorib; Eka Arum Cahyaning Putri (Physical Therapy Journal of Indonesia, 2026)
Background: Carrying school backpacks exceeding 10% of body weight is linked to shoulder discomfort in primary school students. This study aimed to analyse whether factors such as shoulder muscle strength, carrying duration, flexibility, blood lactate levels, and age contribute to shoulder pain beyond backpack load. Methods: This analytical observational study used a cross-sectional design involving 66 male students aged 7–10 years from SDI Maryam Surabaya, Indonesia. Standardised measurements were conducted, including shoulder pain (Wong–Baker Faces Scale), body and backpack weight (digital scale), backpack carrying duration (stopwatch), shoulder strength (dynamometer), flexibility (goniometer), and blood lactate levels (Accutrend Plus). Associations between variables were analysed using Spearman’s rho correlation test. Results: Backpack load percentage (p = 0.020), carrying duration (right p = 0.010; left p = 0.006), age (right p = 0.000; left p = 0.001), and shoulder muscle strength push (p = 0.000) and pull (left p = 0.004) were significantly associated with shoulder pain, while shoulder flexibility and blood lactate showed no significant relationships (p > 0.05). Conclusion: Shoulder pain in primary school students was influenced by backpack load and key physiological factors, particularly shoulder muscle strength, carrying duration, and age. These findings highlighted the importance of preventive measures such as postural education and muscle-strengthening programs to reduce musculoskeletal discomfort from daily backpack use.